Mid-term survival outcome of single-port video-assisted thoracoscopic anatomical lung resection: a two-centre experience. (3rd March 2018) - Wu, Ching Feng; Fernandez, Ricardo; de la Torre, Mercedes; Delgado, Maria; Fieira, Eva; Wu, Ching Yang; Hsieh, Ming Ju; Paradela, Marina; Liu, Yun-Hen; Gonzalez-Rivas, Diego
Abstract: OBJECTIVES: Single-port video-assisted thoracoscopic surgery (SPVATS) anatomical resection has been shown to be a feasible technique for lung cancer patients. Whether SPVATS has equivalent or better oncological outcomes for lung cancer patients remains controversial. The purpose of this study was to evaluate the perioperative and mid-term survival outcomes of SPVATS in 2 different medical centres. METHODS: We retrospectively reviewed patients who underwent SPVATS anatomical resections between January 2014 and February 2017 in Coruña University Hospital's Minimally Invasive Thoracic Surgery Unit (Spain) and Chang Gung Memorial Hospital (Taiwan). Survival outcomes were assessed by pathological stage according to the American Joint Committee on Cancer (AJCC) 7th and 8th classifications. RESULTS: In total, 307 patients were enrolled in this study. Mean drainage days and postoperative hospital stay were 3.90 ± 2.98 and 5.03 ± 3.34 days. The overall 30-day mortality, 90-day morbidity and mortality rate were 0.7%, 20.1% and 0.7%, respectively. The 2-year disease-free survival and 2-year overall survival of the cohort were 80.6% and 93.4% for 1A, 68.8% and 84.6% for 1B, 51.0% and 66.7% for 2A, 21.6% and 61.1% for 2B, 47.6% and 58.5% for 3A, respectively, following the AJCC 7th classification. By the AJCC 8th classification, these were 92.3% and 100% for 1A1, 73.7% and 91.4% for 1A2, 75.2% and 93.4% for 1A3, 62.1% and 85.9% for 1B, 55.6% and 72.7% for 2A, 47.1% and 64.2% for 2B and 42.1% and 60.3% for 3A. CONCLUSIONS: Our preliminary results revealed that SPVATS anatomical resection achieves acceptable 2-year survival outcomes for early-stage lung cancer and is consistent with AJCC 8th staging system 2-year survival data. For advanced stage non-small-cell lung cancer patients, further evaluation is warranted.